Contemporary look at extracorporeal membrane oxygenation as a bridge to reoperative lung transplantation in the United States – a retrospective study - Hayanga, Jeremiah William Awori (Transpl Int, 2020)
The purpose of this study was to examine the influence of extracorporeal membrane oxygenation (ECMO) as a bridge to reoperative lung transplantation (LT) on outcomes and survival. A total of 1960 LT recipients transplanted a second time between 2005 and 2017 were analyzed using the United Network for Organ Sharing (UNOS) Organ Procurement and Transplantation Network (OPTN). Of these recipients, 99 needed ECMO as a bridge to reoperative LT. Mean age was 50 ± 14 years, 47% were females, and the group with ECMO was younger [42 (30–59) vs. 55 (40–62) years]. In both univariate and multivariable analyses (adjusting for age and gender), the ECMO group had greater incidence of prolonged ventilation >48 h (83% vs. 40%, P < 0.001) and in-hospital dialysis (27% vs. 7%, P < 0.001). There were no differences in incidence of acute rejection (15% vs. 11%, P = 0.205), airway dehiscence (4% vs. 2%, P = 0.083), stroke (3% vs. 2%, P = 0.731), or reintubation (20% vs. 20%, P = 0.998). Kaplan–Meier survival analysis showed the ECMO group had reduced 1-year survival (66.6% vs. 83.0%, P < 0.001). After covariate adjustment, the ECMO group only had increased risk for 1-year mortality in the 2005–2011 era (HR = 2.57, 95% CI = 1.45–4.57, P = 0.001). For patients who require reoperative LT, bridging with ECMO was historically a significant predictor of poor outcome, but may be improving in recent years.